The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s43018-022-00443-5
|View full text |Cite
|
Sign up to set email alerts
|

MACHETE identifies interferon-encompassing chromosome 9p21.3 deletions as mediators of immune evasion and metastasis

Abstract: The most prominent homozygous deletions in cancer affect chromosome 9p21.3 and eliminate CDKN2A/B tumor suppressors, disabling a cell-intrinsic barrier to tumorigenesis. Half of 9p21.3 deletions, however, also encompass a type I interferon (IFN) gene cluster; the consequences of this co-deletion remain unexplored. To functionally dissect 9p21.3 and other large genomic deletions, we developed a flexible deletion engineering strategy, MACHETE (molecular alteration of chromosomes with engineered tandem elements).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…Recent data from several groups have found that 9p deletions encompassing 9p21 are significant and selective predictors of ICT resistance in advanced OSCC and lung cancer. 23,24,40,41 This may be due to deletions encompassing the type I interferon gene cluster, 42 which is often co-deleted with the tumor suppressor CDKN2A, highlighting a key mechanism of immune evasion. 43 In our immunogenomic studies, only pretreat- 44 and associated with an immune-cold signal in OSCC 23 that is enhanced by larger deletions extending to the telomeric band at 9p24.1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from several groups have found that 9p deletions encompassing 9p21 are significant and selective predictors of ICT resistance in advanced OSCC and lung cancer. 23,24,40,41 This may be due to deletions encompassing the type I interferon gene cluster, 42 which is often co-deleted with the tumor suppressor CDKN2A, highlighting a key mechanism of immune evasion. 43 In our immunogenomic studies, only pretreat- 44 and associated with an immune-cold signal in OSCC 23 that is enhanced by larger deletions extending to the telomeric band at 9p24.1.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a focal region on chromosome 1 (figure 5d), was significantly amplified in lesions that responded to ICI. Also of interest was the 9p21 locus (45,46), which contains the prominent tumour suppressor CDKN2A, MTAP, as well as a cluster of IFN genes and has been linked to ICI resistance in pan-tumour studies (47). Loss of 9p21 was numerically more frequent in lesions with a lack of response, although this failed to reach significance in a Fisher's exact test (p = 0.08).…”
Section: Identifying Factors Influencing Lesion-specific Responsementioning
confidence: 99%
“… 107 Homozygous deletion of chromosome 9p21.3 has been identified as a candidate biomarker of immunotherapy resistance in several cancers. 108 Tumors with deletion of 9p21.3 exhibit increased resistance to immune checkpoint inhibitors and altered immune infiltrates. The 9p21.3 locus encompasses the suppressor genes CDKN2A and CDKN2B and a cluster of type-I IFN genes.…”
Section: Mechanistic Insights Into Therapy Responsementioning
confidence: 99%
“…To understand the impact of 9p21.3 homozygous loss on pancreatic cancer Scott Lowe and colleagues developed MACHETE (molecular alteration of chromosomes with engineered random repeats), a CRISPR-based approach that enables the targeted deletion of large contiguous genomic regions. 108 Applying MACHETE to a syngeneic mouse model of pancreatic cancer, the Lowe group demonstrated that co-deletion of CDKN2A/CDKN2B and IFN genes combined to both activated cell proliferation and disrupt type-I IFN signaling within the TME. Disruption of type-I IFN signaling was associated with the accumulation of exhausted CD8 + T-cells that express markers of terminal differentiation leading to immune evasion, metastasis, and resistance to immune checkpoint blockade.…”
Section: Mechanistic Insights Into Therapy Responsementioning
confidence: 99%